Effect of harvest period on the eating quality and starch characteristics of Nanjing 3908 - LU Yanli; WANG Qian; DUAN Xiaoliang; ZHANG Dong; SUN Hui (浙江大学学报. 农业与生命科学版)
Rice should be harvested in the best harvest period, either too early or too late, as this can affect quality. In this study, Nanjing 3908 was used to investigate the differences in basic component contents, gelatinization characteristics, thermodynamic characteristics, molecular weight, short-range order and crystal structure of japonica rice harvested in different periods in Nanjing (Jiangsu, China) and Changzhou (Jiangsu, China). The effects of harvest period on rice quality were analyzed. The results showed that the quality of Nanjing 3908 was affected by different planting sites and harvest periods. With delayed harvest, the 1 000-grain mass of samples harvested in the second phase in Nanjing (N-3908-2) was significantly greater than that in the third phase (N-3908-3), while the 1 000-grain mass of samples collected in Changzhou (C-3908-1 to C-3908-3) exhibited no significant changes. The eating qualities of N-3908-2 and C-3908-3 were the best. Compared with N-3908-1, N-3908-2 had a greater protein content, lower hardness, and lower setback of starch after gelatinization. Compared with C-3908-2, C-3908-3 had a greater protein content, unchanged hardness, and enhanced gelatinization ability. In general, with delayed harvest, the gelatinization ability of starch improved, and the eating quality was better, indicating that Nanjing 3908 had an optimal harvest period. Therefore, if eating quality is the main criterion for determining the harvest period, Nanjing 3908 should not be harvested earlier than 65 d after heading. In summary, the optimum harvest period of the same variety was different among the different planting sites. This result provides a theoretical basis for further research on the optimum harvest period of japonica rice.